J31 The effect of football heading on sidestep cutting biomechanics - Ademolu, Grace Adebamiyo; Uiga, Liis; Wood, Greg; Daniels, Kat (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Heading is an integral part of football, with ~20 headers or aerial duels executed per game to intercept, pass or score. However, concerns have recently been raised about the potential short and long-term health impacts of repeated heading. There is evidence suggesting increased risks of sub-concussive trauma – head impacts that do not result in obvious symptoms of concussion but affect cognition and motor function (Montenigro et al., 2017, J Neurotra, 34, 328-340). Repeated heading has been demonstrated to alter brain-muscle communication and affect movement control (Parr et al., 2023, Front Hu Neuro, 17, 1145700) and mechanics of simple tasks such as jumping (Lapointe et al., 2018, Int J Psychophys, 132, 93-98). However, whether these observed cognition and motor impairments translate to the biomechanics of complex multidirectional sport-specific movements such as sidestep cutting is not known. This is an important area to understand because sidestep cutting, an acute change of direction which is ubiquitous in football, is an important performance-determining factor and also a common inciting event for lower-limb injuries (Alentorn-Geli et al., 2009, Knee Sur Sports Trauma, Arth, 17, 705-729) such as the anterior cruciate ligament (ACL) rupture. Due to its propensity to generate high multiplanar knee joint loading during the stance phase of the manoeuvre (Dempsey et al., 2009, Am J Sports Med, 37, 2194-2200), there are often high stresses on the lower limbs which can result in musculoskeletal injury. To date, a copious number of studies have analysed the biomechanics of the sidestep cutting manoeuvre, showing that knee loading is sensitive to the constraints and strategies used to manoeuvre (Dos’Santos et al., 2019, Strength Cond J, 41, 40-54). Accordingly, this present study aims to determine whether there is an effect of repeated heading on sidestep-cutting biomechanics and, if so, the nature of this effect. Participants (n=40) will perform reactive and pre-planned sidestep cutting manoeuvres before completing 15 virtual (n=20) or physical (n=20) ball-heading. They will then repeat the cutting tasks immediately after the bout of heading. Whole-body optical motion capture, ground reaction forces, tri-planar lower-limb joint angles and moments during the stance phase will be analysed to test the effects of football heading on sidestep cutting biomechanics. Results may indicate whether exposure to football heading is a potential risk factor for lower-limb/ACL injury and thus inform the development of training sessions, athlete monitoring, and organisational/national heading guidance and policy for matches and training.